Question
upstudy study bank question image url

Actividades 6. Resuelve las siguientes ecuaciones por el método de igualación: \( \begin{array}{ll}\left.\begin{array}{r}2 x+y=18 \\ \left.\text { a) } \begin{array}{r}4 x-y=0\end{array}\right\}\end{array} \begin{array}{r}x+12 y=-3 \\ x+y=8\end{array}\right\} & \left.\text { c) } \begin{array}{r}5 x+y=10 \\ 2 x-y=4\end{array}\right\} \\ \left.\begin{array}{ll}2 x+y \\ \left.\text { b) } \begin{array}{r}x-2 y=-2 \\ 2 x+y=7 \\ x+y=4\end{array}\right\} & \left.\text { d) } \begin{array}{r}2 x-y=1\end{array}\right\}\end{array} \begin{array}{r}x+y=3 \\ 2 x-y=0\end{array}\right\}\end{array} \)

Ask by Mathis Powell. in Spain
Jan 30,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Here are the solutions for each system of equations using the equalization method: **a)** - Equations: 1. \( 2x + y = 18 \) 2. \( 4x - y = 0 \) - Solution: \( (3, 12) \) **b)** - Equations: 1. \( x - 2y = -2 \) 2. \( 2x + y = 7 \) 3. \( x + y = 4 \) - Solution: No solution **c)** - Equations: 1. \( 5x + y = 10 \) 2. \( 2x - y = 4 \) - Solution: \( (2, 0) \) **d)** - Equations: 1. \( 2x - y = 1 \) 2. \( x + y = 3 \) 3. \( 2x - y = 0 \) - Solution: No solution **Summary of Solutions:** - a) \( (3, 12) \) - b) No solution - c) \( (2, 0) \) - d) No solution

Solution

Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}2x+y=18\\4x-y=0\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}y=18-2x\\4x-y=0\end{array}\right.\) - step2: Substitute the value of \(y:\) \(4x-\left(18-2x\right)=0\) - step3: Simplify: \(6x-18=0\) - step4: Move the constant to the right side: \(6x=0+18\) - step5: Remove 0: \(6x=18\) - step6: Divide both sides: \(\frac{6x}{6}=\frac{18}{6}\) - step7: Divide the numbers: \(x=3\) - step8: Substitute the value of \(x:\) \(y=18-2\times 3\) - step9: Simplify: \(y=12\) - step10: Calculate: \(\left\{ \begin{array}{l}x=3\\y=12\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}x=3\\y=12\end{array}\right.\) - step12: Rewrite: \(\left(x,y\right) = \left(3,12\right)\) Solve the system of equations \( 5 x+y=10;2 x-y=4 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}5x+y=10\\2x-y=4\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}y=10-5x\\2x-y=4\end{array}\right.\) - step2: Substitute the value of \(y:\) \(2x-\left(10-5x\right)=4\) - step3: Simplify: \(7x-10=4\) - step4: Move the constant to the right side: \(7x=4+10\) - step5: Add the numbers: \(7x=14\) - step6: Divide both sides: \(\frac{7x}{7}=\frac{14}{7}\) - step7: Divide the numbers: \(x=2\) - step8: Substitute the value of \(x:\) \(y=10-5\times 2\) - step9: Simplify: \(y=0\) - step10: Calculate: \(\left\{ \begin{array}{l}x=2\\y=0\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}x=2\\y=0\end{array}\right.\) - step12: Rewrite: \(\left(x,y\right) = \left(2,0\right)\) Solve the system of equations \( 2 x-y=1;x+y=3;2 x-y=0 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}2x-y=1\\x+y=3\\2x-y=0\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}y=-1+2x\\x+y=3\\2x-y=0\end{array}\right.\) - step2: Substitute the value of \(y:\) \(\left\{ \begin{array}{l}x-1+2x=3\\2x-\left(-1+2x\right)=0\end{array}\right.\) - step3: Simplify: \(\left\{ \begin{array}{l}3x-1=3\\1=0\end{array}\right.\) - step4: Calculate: \(\left\{ \begin{array}{l}x \in \varnothing \\y \in \varnothing \end{array}\right.\) - step5: Rewrite: \((x, y) \in \varnothing\) Solve the system of equations \( x-2 y=-2;2 x+y=7;x+y=4 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x-2y=-2\\2x+y=7\\x+y=4\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=-2+2y\\2x+y=7\\x+y=4\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left\{ \begin{array}{l}2\left(-2+2y\right)+y=7\\-2+2y+y=4\end{array}\right.\) - step3: Simplify: \(\left\{ \begin{array}{l}-4+5y=7\\-2+3y=4\end{array}\right.\) - step4: Solve the equation: \(\left\{ \begin{array}{l}y=\frac{11}{5}\\-2+3y=4\end{array}\right.\) - step5: Substitute the value of \(y:\) \(-2+3\times \frac{11}{5}=4\) - step6: Simplify: \(\frac{23}{5}=4\) - step7: Calculate: \(\left\{ \begin{array}{l}x \in \varnothing \\y \in \varnothing \end{array}\right.\) - step8: Rewrite: \((x, y) \in \varnothing\) Aquí están las soluciones para cada uno de los sistemas de ecuaciones utilizando el método de igualación: ### a) Sistema de ecuaciones: \[ \begin{align*} 1) & \quad 2x + y = 18 \\ 2) & \quad 4x - y = 0 \end{align*} \] **Solución:** Resolviendo el sistema, encontramos: \[ (x, y) = (3, 12) \] ### b) Sistema de ecuaciones: \[ \begin{align*} 1) & \quad x - 2y = -2 \\ 2) & \quad 2x + y = 7 \\ 3) & \quad x + y = 4 \end{align*} \] **Solución:** Este sistema no tiene solución: \[ (x, y) \in \varnothing \quad \text{(No hay solución)} \] ### c) Sistema de ecuaciones: \[ \begin{align*} 1) & \quad 5x + y = 10 \\ 2) & \quad 2x - y = 4 \end{align*} \] **Solución:** Resolviendo el sistema, encontramos: \[ (x, y) = (2, 0) \] ### d) Sistema de ecuaciones: \[ \begin{align*} 1) & \quad 2x - y = 1 \\ 2) & \quad x + y = 3 \\ 3) & \quad 2x - y = 0 \end{align*} \] **Solución:** Este sistema no tiene solución: \[ (x, y) \in \varnothing \quad \text{(No hay solución)} \] ### Resumen de soluciones: - a) \( (3, 12) \) - b) No hay solución - c) \( (2, 0) \) - d) No hay solución

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

Para resolver las ecuaciones por el método de igualación, comenzamos despejando una de las variables en una de las ecuaciones y luego igualamos las expresiones obtenidas. Aquí te dejo la resolución de cada grupo de ecuaciones: a) De \(2x + y = 18\) despejamos \(y = 18 - 2x\). Luego, en \(4x - y = 0\) sustituimos \(y: 4x - (18 - 2x) = 0 \Rightarrow 4x + 2x = 18 \Rightarrow 6x = 18 \Rightarrow x = 3\). Sustituyendo en \(y = 18 - 2(3) = 12\). Así que la solución es \(x = 3\) y \(y = 12\). b) Despejamos \(y\) en \(x + y = 4\) así que \(y = 4 - x\). Sustituyendo en \(x - 2y = -2\): \(x - 2(4 - x) = -2 \Rightarrow x - 8 + 2x = -2\) \(3x = 6 \Rightarrow x = 2\). Sustituyendo en \(y = 4 - 2 = 2\). La solución es \(x = 2\) y \(y = 2\). c) Despejamos \(y\) en \(5x + y = 10\) así que \(y = 10 - 5x\). Sustituyendo en \(2x - y = 4\): \(2x - (10 - 5x) = 4 \Rightarrow 2x - 10 + 5x = 4\) \(7x = 14 \Rightarrow x = 2\). Sustituyendo en \(y = 10 - 5(2) = 0\). Así que la solución es \(x = 2\) y \(y = 0\). d) Despejamos \(y\) en \(x + y = 3\) así que \(y = 3 - x\). Sustituyendo en \(2x - y = 1\): \(2x - (3 - x) = 1 \Rightarrow 2x - 3 + x = 1\) \(3x = 4 \Rightarrow x = \frac{4}{3}\). Sustituyendo en \(y = 3 - \frac{4}{3} = \frac{5}{3}\). La solución es \(x = \frac{4}{3}\) y \(y = \frac{5}{3}\). ¡Es un viaje numérico impresionante! Si necesitas más ayuda, aquí estoy.

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy